2019
DOI: 10.1098/rsbl.2019.0148
|View full text |Cite
|
Sign up to set email alerts
|

Yucatán carnivorans shed light on the Great American Biotic Interchange

Abstract: The Great American Biotic Interchange is considered to be a punctuated process, primarily occurring during four major pulses that began approximately 2.5 Ma. Central America and southeastern Mexico have a poor fossil record of this dynamic faunal history due to tropical climates. Exploration of submerged caves in the Yucatán, particularly the natural trap Hoyo Negro, is exposing a rich and remarkably well-preserved late Pleistocene fauna. Radiometric dates on megafauna range from approximately 38 400–12 850 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…In addition to evidence for hybridisation between Tremarctos and ursine bears, we also recovered convincing evidence for hybridisation between Arctotherium and Tremarctos (Table 1) [5,38], however, the extent of occupation by both genera in the region is unknown, and conceivably Central America represents a contact zone between the genera throughout the Pleistocene where hybridisation may have occurred.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…In addition to evidence for hybridisation between Tremarctos and ursine bears, we also recovered convincing evidence for hybridisation between Arctotherium and Tremarctos (Table 1) [5,38], however, the extent of occupation by both genera in the region is unknown, and conceivably Central America represents a contact zone between the genera throughout the Pleistocene where hybridisation may have occurred.…”
Section: Resultssupporting
confidence: 53%
“…This result suggests that no gene flow occurred between Arctodus or Arctotherium and the ancestors of any modern ursine bear, and also demonstrates a lack of any discernible reference bias in the ancient genomic data (which would result in asymmetrical allele sharing with the reference). Thus, it appears Arctodus and Arctotherium did not hybridise with brown and black bears in the Americas during the late Pleistocene, even though the distribution of Arctodus overlapped with both ursines, and Arctotherium may have encountered them in Mexico or Central America [5] Contrary to previous studies, our D-statistics revealed signals consistent with gene flow between the spectacled bear and members of Ursinae (Table 1 & S5), suggesting the possibility that Tremarctos hybridised with ancestors of either the brown bear or American black bear during the Pleistocene. This signal is surprising given the deep divergence between ursine and short-faced bears, having split approximately 10 million years ago (mya) [12,14,28].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Exploration of submerged caves by technical divers in the Yucatán of Mexico has resulted in a number of fossil discoveries and recent publications. This includes early humans (Homo sapiens) in the Americas (e.g., Chatters et al, 2014;González González et al, 2013;Stinnesbeck et al, 2017a), and extinct fauna: 1) new types of giant ground sloths, Nohochichak xibalbahkah (McDonald et al, 2017), Xibalbaonyx oviceps (Stinnesbeck et al, 2017b), and Xibalbaonyx exinferis (Stinnesbeck et al 2020), 2) a new peccary, Muknalia minima (Stinnesbeck et al, 2017c), 3) a new jaguar, Panthera balamoides (Stinnesbeck et al, 2018a; but questioned as a possible ursid by Schubert et al, 2019 andRuiz-Ramoni et al, 2020), and 4) short-faced bears (Arctotherium wingei) and canids (Protocyon troglodytes) that were previously only known from the South American fossil record (Schubert et al, 2016;Schubert et al, 2019).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Our team's Yucatán research has focused primarily on Hoyo Negro, a natural pit inside the submerged Sac Actun cave system, Quintana Roo, Mexico (Chatters et al, 2014;McDonald et al, 2017;Schubert et al, 2019). As Hoyo Negro contains fossil peccary skeletons, we were curious whether or not this pit may also record the recently described new genus and species (Muknalia minima) reported to occur in the same region (Stinnesbeck et al, 2017c).…”
Section: Introduction Backgroundmentioning
confidence: 99%